Порівняння методів модуляції квазіімпедансного інвертора в автономній системі живлення з накопичувачами електроенергії - Zakharchenko, Dmytro; Stepenko, Serhii (PE "Politekhperiodika", Book and Journal Publishers, 2025)
This paper presents a comprehensive study of a modern autonomous power supply system with energy storage devices, focusing on all significant components within the system. Modern inverter control systems are described, highlighting the advantages and disadvantages of each method, the calculation approaches for key parameters, and the proposed implementation of control systems using MatLab/Simulink software. The modeling of control systems for a two-level quasi-impedance inverter within an autonomous power supply system with energy storage is conducted.Based on the simulation results for powering a 2 kW AC load (220 V, 50 Hz) using lithium-ion energy storage and various control methods, a comparative table of the main performance indicators of modulation techniques is provided. Under the specified system requirements, the optimal control method is simple boost control (SBC), which offers the best efficiency among the considered techniques while maintaining low total harmonic distortion and a low implementation complexity.It should be noted, however, that in real-world applications, the choice of modulation technique for a quasi-impedance inverter depends not only on conversion efficiency but also on practical constraints. For example, pulse-width modulation (PWM), the simplest to implement, lacks voltage-boosting capability due to the absence of shoot-through mode, reducing its effectiveness in low-input-voltage systems and potentially degrading output quality under high load. SBC, in turn, is limited by the absence of a zero switching state, increasing stress on passive inverter components. Additionally, the simultanІeous activation of all transistors during shoot-through mode leads to higher thermal losses and increased cooling requirements.The practical application of constant boost control (CBC), which extends the voltage gain range by adding a third harmonic to the modulation signal, is hindered by higher harmonic distortion (up to 6.8%) and the need for additional filtering. Moreover, its implementation is more complex and demands precise parameter tuning for stable operation.Other techniques, such as maximum boost control (MBC) and maximum constant boost control (MCBC), although capable of achieving the highest voltage gain, introduce significant low-frequency ripples, complicating passive component design, and cause considerable switching losses due to simultaneous key activation. These methods are more suitable for stationary systems with robust cooling and high-quality filtering.The results of this study can support the justified selection of optimal modulation techniques for autonomous power systems with energy storage devices.